Flow cytometric analysis of morphologic and immunological characterisation of the tiger shrimp Penaeus monodon haemocytes - Jian-An Xian; Pei-Hua Zheng; Yao-Peng Lu; Jun-Tao Li; Ze-Long Zhang; Xiu-Xia Zhang; Dong-Mei Wang; Lei Wang (Aquaculture Reports, 2021)
Morphology and immune functions of Penaeus monodon haemocytes were analysed by flow cytometry (FCM). Basing on the relative size and granularity, there are three types of haemocyte identified by FCM, including hyaline cells (HC), semigranular cells (SGC) and granular cells (GC). GC and SGC were significantly larger than HC. GC contained more granules in the cytoplasm than the two other types. SGC were the most abundant cells, while HC were the least. The mean total apoptotic cell ratio was 5.09 % in the fresh shrimp haemocytes. SGC contributed most to the phagocytic activity, and HC contributed least, probably due to the great difference of percentage. GC had most mass of mitochondria and lysosome, and HC contained least. Defined by different characteristic of lysosomal mass, three subsets of haemocytes were observed. GC were most active in non-induced and zymosan-induced reactive oxygen species (ROS) production, while HC showed lowest oxidative activity. Both non-induced and zymosan-induced esterase activity (EA) in GC were higher than those in SGC and HC. The present flow cytometric analysis clearly demonstrated the variation in morphologic and immunological characterisation among the three haemocyte subpopulations. The facts that SGC account for most of the number of circulating haemocyte, while GC contain most organelles in relation to energy supply and immune defence, and have highest immune activites, suggesting that GC and SGC are the main haemocyte types involved in the cellular defence of P. monodon.